2012
DOI: 10.1103/physrevb.85.014512
|View full text |Cite
|
Sign up to set email alerts
|

Spin-flip scattering and critical currents in ballistic half-metallicd-wave Josephson junctions

Abstract: We analyze the dc Josephson effect in a ballistic superconductor/half-metal/superconductor junction by means of the Bogoliubov-de Gennes equations. We study the role of spin-active interfaces and compare how different superconductor symmetries, including d-wave pairing, affect the Josephson current. We analyze the critical current as a function of junction width, temperature, and spin-flip strength and direction. In particular, we demonstrate that the temperature-dependence of the supercurrent in the dxy-symme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…Here a i ( i = 1, 2, 3, 4) with is the Andreev reflection coefficient without flip for electron up incident in left superconductor, similarly is the Andreev reflection coefficient without flip for electron down incident in left superconductor, and are the Andreev reflection coefficients without flip for hole up and hole down incident in left superconductor respectively. There are other ways of writing the Josephson supercurrent formula in Furusaki-Tsukuda approach 19 , 20 , all such ways give identical total Josephson current. These different ways involve different scattering amplitudes, as due to the fact that Furusaki-Tsukuda procedure obeys both detailed balance as well as probability conservation, allowing for the possibility of different representations of the same formula.…”
Section: Josephson Current In Presence Of a Hsmmentioning
confidence: 99%
See 1 more Smart Citation
“…Here a i ( i = 1, 2, 3, 4) with is the Andreev reflection coefficient without flip for electron up incident in left superconductor, similarly is the Andreev reflection coefficient without flip for electron down incident in left superconductor, and are the Andreev reflection coefficients without flip for hole up and hole down incident in left superconductor respectively. There are other ways of writing the Josephson supercurrent formula in Furusaki-Tsukuda approach 19 , 20 , all such ways give identical total Josephson current. These different ways involve different scattering amplitudes, as due to the fact that Furusaki-Tsukuda procedure obeys both detailed balance as well as probability conservation, allowing for the possibility of different representations of the same formula.…”
Section: Josephson Current In Presence Of a Hsmmentioning
confidence: 99%
“…Neglecting the contribution from incoming quasiparticle 20 and inserting the wave function into the boundary conditions, we get a homogeneous system of 24 linear equations for the scattering amplitudes. If we express the scattering amplitudes in the two normal metal regions by the scattering amplitudes in the left and right superconductor we get a homogeneous system of 8 linear equations 17 , where x is a 8 × 1 column matrix and is given by and M is a 8 × 8 matrix which is explicitly written in supplementary material section II.…”
Section: Josephson Current In Presence Of a Hsmmentioning
confidence: 99%
“…This resembles the situation in, for instance, SFIFS junctions with parallel or anti-parallel alignment of the exchange fields of the two ferromagnets, 8 or SIFIS junctions where the interfaces are spin-active. 9 In odd junctions, the subgap states are spin-split, while for even junctions, the states are spin degenerate. Naively, odd junctions are thus equivalent to ferromagnetic junctions, as there is a net magnetic moment (albeit weak) if one averages over the junction length.…”
mentioning
confidence: 99%
“…[1][2][3] In conventional S/F/S junctions, the currents are always carried by pairs of electrons in a spin singlet state and decay very rapidly in the F, which normally prohibits the existence of singlet pairs. It has been predicted that this rapid spatial decay would not occur if the spin triplet proximity effect exists in the F. [3][4][5][6][7][8][9][10][11] Long-ranged triplet supercurrents have been demonstrated by several experimental works in a wide-range of Fs, including a Co/Ru/Co synthetic antiferromagnet interfaced by normal metal spacers and ferromagnetic alloys; 12 a Ho/Co/Ho composite barrier 13 or the Ho wires with interfaces to conventional superconductors; 14 a magnetic Cu 2 MnAl Heusler compound; 15 a half metallic CrO 2 (Refs. 16 and 17); and a Co nanowire.…”
mentioning
confidence: 99%
“…19 Triplet superconducting proximity effect then requires an AR process that includes a spin flip. 3,4 A number of mechanisms that give rise to the spin flip AR required for the triplet superconducting proximity effects, such as magnetic domain walls, 4 spin-orbit interaction in noncentrosymmetric superconductors, 9 and a rotating magnetization in the F close to the interface, 10,11 have been investigated in hybrid F/S systems. Effects of Rashba spinorbit coupling (RSOC) in noncentrosymmetric superconductors, such as CePt 3 Si and Li 2 Pd 3 B, have been investigated, and it was found that superconducting pair potential becomes a mixture of spin singlet even parity and spin triplet odd parity.…”
mentioning
confidence: 99%